Joint decision on contraceptive use and determinant factors among married women of reproductive ages (15-49) in Ethiopia: a multilevel analysis using Ethiopian Demographic and Health Survey; 2016 data - Melaku Hunie Asratie; Getayeneh Antehunegn Tesema; Daniel Gashaneh Belay (BMC, 2024)
Abstract Background Contraceptive usage in Ethiopia is significantly influenced by the decision-maker at the household level. Joint decision-making involving both women and their husbands/partners is considered ideal for improving contraceptive uptake among women and for managing health outcomes related to contraceptive side effects. However, there is a lack of substantial evidence regarding the prevalence and impact of joint decision-making on contraceptive use in Ethiopia. Therefore, the current study aimed to assess the magnitude of joint decision-making on contraceptive use and its determinant factors among married, contraceptive-using, reproductive-age women in Ethiopia. Methods This study was conducted based on the Ethiopian Demographic and Health Survey (EDHS) 2016 data. A total weighted sample of 3,669 married, contraceptive-using, reproductive-age women were included in the study. Multilevel logistic regression was employed due to the hierarchical nature of the data. Variables with a p-value of ≤ 0.2 in the bivariate multilevel analysis were included in the multivariable multilevel analysis. The adjusted odds ratio (AOR) with a 95% confidence interval (CI) was used to determine the direction and strength of associations. Variables with a p-value of < 0.05 in the multivariable multilevel analysis were considered statistically significant for joint decision-making on contraceptive use. Results The prevalence of joint decision-making on contraceptive use in Ethiopia was 78.81% [95% CI: 71.35-74.23%]. Several factors were found to be statistically significant in relation to joint decision-making on contraceptive use: Women educational level primary, secondary, and higher (Adjusted odds' ratio (AOR = 1.5; CI 1.2-1.9), (AOR = 1.9; CI 1.3-2.9), and (AOR = 2.1; CI 1.2-3.5) respectively, protestant in religion (AOR = 1.7; CI 1.7-2.5), wealth status rich (AOR = 1.4; CI 1.1-1.9), media exposure (AOR = 1.4; CI 1.1-1.9), and community poverty high (AOR = 0.6; CI 0.6-0.9). Conclusions In Ethiopia, the majority of contraceptive users are married, reproductive-age women, and their decision to use contraceptives is typically made jointly with their husbands or partners. Factors positively associated with joint decision-making on contraceptive use include women's educational level (primary, secondary, and higher), being Protestant, having a higher wealth status, and media exposure. Conversely, women living in communities with high poverty levels are less likely to make joint decisions about contraceptive use. Health care providers, health care programmers and policy makers should be focused on these determinant factors to enhance joint decision-making in women's contraceptive use in Ethiopia.